Prolonged Alteration of Neonate Traits Following Maternal Exposure to Fishing-Capture Stress During Late Pregnancy in a Chondrichthyan Species - Finotto, Licia; Walker, Terence Ivan; Reina, Richard David (Frontiers in Marine Science, 2021)
For animals discarded after fishing capture (unwanted bycatch), the effects of fishing-capture stress can extend beyond immediate or delayed death, causing long-term, sub-lethal effects such as injuries and physiological, behavioral, immune, energetic, and reproductive consequences. Given the importance of successful reproduction for population recruitment, investigating reproductive impairment is essential, even more so for animals with low reproductive rates such as chondrichthyans. However, data for these species are lacking, even though the poor conservation status of many chondrichthyan populations and the threats from overexploitation and discard require a better understanding of fishing-capture stress consequences. In this study, we investigated the reproductive consequences of trawling and air exposure stress when experienced by southern fiddler rays (Trygonorrhina dumerilii) during late pregnancy, with a focus on neonatal traits. Compared with neonates from unstressed mothers, neonates born from mothers subjected to capture simulation had significantly lower body mass and yolk sac volume at birth, showed a granulocyte-to-lymphocyte ratio indicative of a stressed condition, reduced growth, altered burying behavior, reduced boldness, and swam for shorter distances after a simulated predator attack. Smaller size and lower growth rate might expose neonates to a higher rate of predation, and similarly, the altered burying and swimming behaviors may reduce their ability to escape from predators. Decreased boldness could impact neonate survival by reducing their ability to compete and obtain food and resources. Further investigations are needed, but these initial results suggest that capture stress suffered by pregnant rays may alter traits and survival of their offspring with consequences for recruitment and population abundance.